Gas flow in near surface comet like porous structures: Application to 67P/Churyumov-Gerasimenko. (15th October 2018) - Christou, Chariton; Dadzie, S. Kokou; Thomas, Nicolas; Marschall, Raphael; Hartogh, Paul; Jorda, Laurent; Kührt, Ekkehard; Wright, Ian; Rodrigo, Rafael
Abstract: We performed an investigation of a comet like porous surface to study how sub-surface sublimation with subsequent flow through the porous medium can lead to higher gas temperatures at the surface. A higher gas temperature of the emitted gas at the surface layer, compared to the sublimation temperature, will lead to higher gas speeds as the gas expands into the vacuum thus altering the flow properties on larger scales (kilometres away from the surface). Unlike previous models that have used modelled artificial structures, we used Earth rock samples with a porosity in the range 24–92% obtained from X-ray micro computed tomography (micro-CT) scans with resolution of some μm. Micro-CT scanning technology provides 3D images of the pore samples. The direct simulation Monte Carlo (DSMC) method for the rarefied gas dynamics is directly applied on the digital rock samples in an unstructured mesh to determine the gas densities, temperatures and speeds within the porous medium and a few centimetres above the surface. The thicknesses of the rock samples were comparable to the diurnal thermal skin depth (5 cm). H2 O was assumed to be the outgassing species. We correlated the coma temperatures and other properties of the flow with the rock porosities. The results are discussed as an input to analysis of data from the Microwave Instrument on Rosetta Orbiter (MIRO) on the 67P/Churyumov- Gerasimenko. Highlights: Comet outgassing properties are related with the comet material porosity. Effects of the porosity on the outgassing flow properties are non-linear. Coupled phenomenon exists in terms of temperature and density for porous medium with low porosity. Future missions should measure gas properties at various distances above surface.